A Novel Hydrogen Peroxide Amperometric Sensor Based on Hierarchical 3D Porous MnO2−TiO2 Composites. Issue 5 (29th January 2019) - Ko, Wen‐Yin; Chen, Yi‐Shin; Li, Meng‐Shan; Lai, Jun‐Yan; Lin, Kuan‐Jiuh
Abstract: A novel nanocomposite electrode based on hierarchical 3D porous MnO2 −TiO2 for the application in hydrogen peroxide (H2 O2 ) sensors has been explored. This electrode was fabricated by growing TiO2 cross‐linked nanowires on a commercial fluorine tin oxide (FTO) glass via a hydrothermal process and subsequent deposition of 3D honeycomb‐like MnO2 nanowalls using an electrodeposition method (denoted as 3D MNS‐TNW@FTO). The obtained 3D MNS‐TNW@FTO electrode was characterized by scanning electron microscopy (SEM), Raman spectroscopy, X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy (XPS). Based on such a unique 3D porous framework and the existence of MnO2, the electrode demonstrates a good performance in the detection of H2 O2, with two linear ranges from 9.8 to 125 μM and 125 μM–1.0 mM, a good selectivity of 8.02 μA mM −1  cm −2, and a low detection limit of 4.5 μM. In addition, the simplicity of the developed low‐cost fabrication process provides an efficient method for the mass production of electrocatalytical MnO2 −TiO2 nanocomposites on commercial FTO glass for H2 O2 sensing applications and can be adapted for other electrochemical sensors for various biochemical targets. It thus is beneficial for the practical usage in bioanalysis. Abstract :